IMPLEMENTASI NILAI-NILAI KARAKTER BUDDHIS PADA SISWA SMP PERGURUAN BUDDHIS BODHICITTA MEDAN - Sumiati Chandra; Nuriani; Joko Santoso; Lamirin (Jurnal Genta Mulia, 2026)
This study aims to describe the values of Buddhist character that have been implemented and to find out how they are applied to grade VII junior high school students at Medan Bodhicitta Buddhist College. This research was carried out at Medan Bodhicitta Buddhist College in the 2022/2023 academic year. This study used descriptive qualitative method. This study obtained data by data collection techniques through observation, interviews and documentation. The subjects of this study were school principals, teachers of Buddhism and ethics, and students of junior high school grade VII of Medan Bodhicitta Buddhist College. Data analysis techniques used are data collection, data reduction, data presentation and data verification / conclusions. The results of this study show that Buddhist character values such as responsibility, discipline, hard work, friendship, tolerance & peace-loving, and religious have been applied to junior high school students in grade VII of college Buddhist Bodhicitta Medan. This is evident from the daily attitude of students such as completing tasks and obligations on time, daring to admit mistakes, discipline in terms of time , not differentiating – Distinguish the background/social status of fellow friends, study hard, respect and respect fellow friends who have different beliefs and also actively participate in religious activities that held in schools and monasteries.